Special Education Teacher Leadership Practice: A Malaysian Study. - Keow Ngang Tang; Ching Mey See (International Journal of the Humanities, 2009)
A descriptive study using questionnaires was conducted in 2008 to assess the perception and the implementation of teacher leadership practice displayed by integrated special education program teachers in the four regions of Malaysia. Creating energy in the classroom dimension, building capacity dimension, securing environment dimension, extending the vision dimension, meeting and minimising crisis dimension, and seeking and charting improvement dimension were key variables as teacher leadership dimensions that guided the study. Respondents were 369 integrated special education program school teachers. Data were analyzed descriptively through the use of the Statistical Package for Social Sciences (SPSS) program using frequencies, percentages, mean, and t-test. The results reveal that the integrated special education program teachers not only practising but also applying all the six dimensions of teacher leadership at high level. Based on the t-test analysis, there is a significant difference between the level of agreement and the level of implementing the teacher leadership practice. This study indicates the importance of studying teacher leadership as the information collected would help the integrated special education teachers to practise, implement, access and maintain high level of teacher leadership which in turn to promote better classroom management.